Mapping mineral resources in a living land : Sami mining resistance in Ohcejohka, northern Finland - Lassila, Maija M. (Geoforum, 2018)
During the past decade, Finland has been the target of a global boom in the quest for untapped mineral resources. Based on the mapped information of mineral potential provided by the state, multinational mining corporations are making reservations for and conducting mineral explorations particularly in Finland’s peripheral regions. This paper investigates the emergence of an anti-mining movement in Ohcejohka, in northernmost Finland, in 2014–2015, and the ontological conflict manifested in the outside mapping of the land as “mineral rich” as well as the local people's various knowledges of the land as a lived place. By producing a holistic counter-mapping of their social, ancestral and meaningful landscape, the movement questioned the state’s and the company’s homogenising knowledge in the production of land and resources. While the reality-making effects of modern maps have previously been studied, the entanglements of such mappings in environmental conflicts with local ontological realities and knowledge spheres have not been extensively studied. This paper argues that rather than imposing a “one world ontology”, maps and mappings of land and resources are culmination points in environmental conflicts, where they become renegotiated, challenged and redefined in the local and dynamic enactments of reality. Peer reviewed